Cytohistology of interaction between Cucurbita moschata and Sphaerotheca fuliginea ascosporal infection - T.H. BHAGIRATH, A. KABITARANI and (Indian Phytopathology, 2002)
Mechanism and process of infection of Cucurbita moschata by ascospore of Sphaerotheca [uliginea were studied using whole mount and sections. Infection of Cucurbita moschata with ascospore of Sphaerotheca fuliginea consists of ascospore germination, penetration of host cell by ascosporal germ tube, development of vegetative hyphae from ascosporal body and penetration of host cell by these vegetative hyphae. Penetration of host cell by ascosporal germ tube is entirely mechanical which results into dislocation and inward invagination of epidermal cell. Epidermal cells that are in contact with the tip of germ tube considerably increase in size. The affected host cells do not form papilla. The infection peg does not form haustorium but forms a number of hypha - like branches that extend to neighbouring epidermal cells and formed primary hyphae. From the primary hyphae anamorph developed.